Engaging With Contemporary Dance: What Can Body Movements Tell us About Audience Responses? - Theodorou, Lida (Front Psychol, 2019)
In live performances seated audiences have restricted opportunities for response. Some responses are obvious, such as applause and cheering, but there are also many apparently incidental movements including posture shifts, fixing hair, scratching and adjusting glasses. Do these movements provide clues to people's level of engagement with a performance? Our basic hypothesis is that audience responses are part of a bi-directional system of audience-performer communication. This communication is part of what distinguishes live from recorded performance and underpins live performers' moment-to-moment sense of how well a performance is going. Here we investigate the range of visible real-time movements of audiences in four live contemporary dance performances. Video recordings of performers and audiences were analyzed using computer vision techniques for extracting face, hand and body movement data. The meaning of audience movements were analyzed by comparing clips of the audience at moments of maximum and minimum movement to expert and novice judges. The results show that audience clips with the lowest overall movement are judged as displaying the highest engagement. In addition, we found that while there is no systematic relationship between audience and dancers movement, hands seem to play an especially significant role since they move significantly more compared to the rest of the body. We draw on these findings to argue that collective stillness is an especially salient signal of audience engagement.